Gugurnya Hak Menuntut Terhadap Korporasi Akibat Pailit - Ismail, Audaraziq; Zulfa, Eva Achjani; Yutcesyam, Yutcesyam; Lazira, Fatiatulo (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
Prosecution is basically an action by the public prosecutor to delegate a criminal case to the competent District Court so that it is examined and decided by a judge in a court session. With regard to prosecution, Article 109 of the Criminal Procedure Code states that there are 3 reasons for stopping prosecution, namely that an event is not a criminal act, there is not enough evidence collected by investigators to prove the fulfillment of the elements in a criminal act and for the sake of law. The Criminal Code, First, with regard to the application of the principle of ne bis in idem. Second, if the Defendant dies, Third, Expires, Fourth, Settlement outside the court, Article 82 of the Criminal Code has described if an offense is threatened with a fine only, then prosecution can be avoided by paying the maximum fine directly. Against corporations, prosecution is limited by a number of provisions, in this case also including when the corporation is bankrupt. That as a result, if the entire corporate assets are included in the bankruptcy code, there will be a transfer of corporate licenses and an impact on the liquidation process. Thus, based on the provisions of Article 142 paragraph (1) of Law no. 40 of 2007 concerning Limited Liability Companies, the corporation is dissolved. Thus, the prosecution of the bankrupt corporation can be dropped.